An Ordinance Relating to Offenses and Disorderly Conduct, Olympia City Council, Ordinance No. 152, § 3 (Washington, 1882). - (:unkn) unknown (My University, 1882)
Any [per]son who shall, in the usual walks3 of life, within the limits of the City of Olympia carry any deadly weapon concealed about his person, shall be liable to a fine of not more than ten or less than five dollars
Keywords: CARRY - CONCEALED